Prenatal diagnosis and molecular genetic analysis of short rib-polydactyly syndrome type III (Verma-Naumoff) in a second-trimester fetus with a homozygous splice site mutation in intron 4 in the NEK1 gene - Chih-Ping Chen; Schu-Rern Chern; Tung-Yao Chang; Yi-Ning Su; Yi-Yung Chen; Jun-Wei Su; Wayseen Wang (Elsevier, 2012)
Objective: To demonstrate perinatal imaging findings and to investigate the mutation in the NEK1 gene in a fetus with type III short rib-polydactyly syndrome (SRPS) (Verma-Naumoff). Case Report: A 34-year-old woman with no past history of fetal SRPS was referred to the hospital at 21 weeks of gestation because of sonographic diagnosis of short limbs in the fetus. Fetal ultrasound revealed a narrow thorax, short ribs, short limbs with marginal spurs, and postaxial hexadactyly in both the hands and feet. A diagnosis of SRPS III (Verma-Naumoff) was made. Amniocentesis was performed. The karyotype was 46,XY. Molecular genetic analysis of the amniotic fluid cells identified a homozygous splice site mutation in intron 4 (c.331-1 A > G) or IVS4-1 A > G in the NEK1 gene. The parents were heterozygous for the mutation. The pregnancy was subsequently terminated and a malformed fetus was delivered with prominent forehead, a flattened nasal bridge, a narrow and short trunk, a protuberant abdomen, bilateral postaxial polydactyly and syndactyly of the hands and feet, and micromelic limbs. No facial cleft or genital abnormality was noted. The radiograph was consistent with SRPS III. Conclusion: Polydactyly, micromelia, metaphyseal spurs, widened humeral metaphyses, and shortened ribs can be prominent prenatal ultrasound findings of SRPS III. The present case provides evidence for a correlation of a mutation in the NEK1 gene with SRPS III.